Properties of a certain product of submodules - Heidari, S.; Nikandish, R.; Nikmehr, M.J. (Український математичний журнал, 2011)
Let R be a commutative ring with identity, M an R-module and K1, . . . , Kn submodules of M. In this article,
we construct an algebraic object, called product of K1, . . . , Kn. We equipped this structure with appropriate
operations to get an R(M)-module. It is shown that R(M)-module Mⁿ = M . . . M and R-module M
inherit some of the most important properties of each other. For example, we show that M is a projective (flat)
R-module if and only if Mⁿ is a projective (flat) R(M)-module Припустимо, що R — комутативне кiльце з одиницею, M — R-модуль i K1, . . . , Kn — пiдмодулi M. Побудовано алгебраїчний об’єкт, що називається добутком пiдмодулiв K1, . . . , Kn. Цю структуру оснащено вiдповiдними операцiями для отримання R(M)-модуля. Показано, що R(M)-модуль
Mⁿ = M . . . M та R-модуль M успадковують деякi з найбiльш важливих властивостей один одного.
Наприклад, показано, що M є проективним (плоским) R-модулем тодi i тiльки тодi, коли Mⁿ —
проективний (плоский) R(M)-модуль.